2011
DOI: 10.1166/jnn.2011.3853
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal and Morphological Characterization of Polycarbonate/Oxidized Carbon Nanofiber Composites Produced with a Lean 2-Step Manufacturing Process

Abstract: In this study we report the advantages of a 2-step method that incorporates an additional process pre-conditioning step for rapid and precise blending of the constituents prior to the commonly used melt compounding method for preparing polycarbonate/oxidized carbon nanofiber composites. This additional step (equivalent to a manufacturing cell) involves the formation of a highly concentrated solid nano-nectar of polycarbonate/carbon nanofiber composite using a solution mixing process followed by melt mixing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Therefore, the interaction between CNFs and the PVDF matrix was enhanced. Even with the functionalized CNFs, we also found that the interaction could be poor when entanglements/agglomerates existed due to an ineffective processing method 22. In this study and our other reported work, it was found that improving the dispersion could also improve the interaction between the nanofillers and the polymer matrix materials.…”
Section: Resultssupporting
confidence: 47%
“…Therefore, the interaction between CNFs and the PVDF matrix was enhanced. Even with the functionalized CNFs, we also found that the interaction could be poor when entanglements/agglomerates existed due to an ineffective processing method 22. In this study and our other reported work, it was found that improving the dispersion could also improve the interaction between the nanofillers and the polymer matrix materials.…”
Section: Resultssupporting
confidence: 47%
“…In addition to the observance of the loss modulus curves, examining the area under the loss modulus curves can expose the different damping behavior exhibited by the nanocomposites . The area values demonstrate the material's ability to convert mechanical energy into heat through molecular motion .…”
Section: Resultsmentioning
confidence: 99%
“…14,15,[24][25][26][27][28][29][30][31] Additionally, it has been demonstrated that this method may bring very high accuracy for the analysis of systems with high amounts of large agglomeration which is commonly found in masterbatches. 5,22 Therefore, this new approach is likely to be highly effective for use with two-step processes and practical for various sample preparation procedures for optical microscopy making it broadly applicable for industry assessment.…”
Section: Introductionmentioning
confidence: 99%
“…A popular process aimed to improve the industry friendliness of nanocomposite manufacturing involves dividing the manufacturing process into two steps: step one creates a well dispersed nanocomposite commonly named a masterbatch and the second step distributes and/or dilutes the masterbatch with the neat polymer to achieve the final nanocomposite at a desired loading. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] There are several benefits to industry with this two-step process: (1) the dispersion of the nanofiller can be handled separately from the distribution meaning current polymer production equipment can be used for the second step, (2) the manufacturing is practical for high volume industry processes, and (3) safety is increased for the second step because nanofillers do not need to be directly handled in their nano-form. Masterbatches are already commercially available for several polymer and nanofiller combinations, but there are no published methods or standards for assessing masterbatch quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation